Teoria de médio alcance para o cuidado de enfermagem à criança com cardiopatia congênita - Nascimento, Maria Naiane Rolim (2024)
The study seeks to fill the gap in knowledge regarding the development of the Middle Range Theory (TMA) of nursing for children with congenital heart disease. It is intended to contribute to pediatric care based on a reflective and critical look at the use of nursing theories. The hypothesis of the study is: whether the development of a TMA, based on research induction, using a pre-existing concept, analyzed based on the literature and with propositions, assumptions and modeling is applicable to nursing care for children with congenital heart disease. Therefore, the objective was to develop a TMA for nursing care for children with congenital heart disease through research induction. To this end, a multiple methods study was carried out, organized in three stages: 1) scope review; 2) concept analysis; and, 3) development of the nursing TMA. In the first stage, a scope review was carried out following the eight steps recommended by the Joanna Briggs Institute. In the second stage, the concept <care for children with congenital heart disease= was analyzed through eight phases by Walker and Avant (2019). The third stage included a theoretical or basic approach to the development of the theory, with the structuring of the theory: purpose and context of theory generation; theoretical propositions; layout; assumptions; and practical application of theory. The results were presented according to the study stages. In the Scope Review, 66 studies were identified, of which 82 nursing care were extracted, organized based on the concepts of cardiological assessment (06), preventive care (38), intensive care (16) and palliative care (22). In the Analysis of the Concept of Nursing Care for Children with Congenital Heart Disease, 10 antecedents, four attributes, six consequences in the short term and five in the medium and long term were identified. Based on the findings of the previous stages, the TMA emerged for the care of children with congenital heart disease, with the purpose of serving as a theoretical foundation to guide nursing and health care in children affected with congenital heart disease, acting from the promotion health, such as self-care, the prevention of cardiovascular and respiratory complications, and also the prevention of other risks related to the condition, as well as the process of frequent hospitalization. The aim of this study was to enable, based on the clinical-epidemiological reality of the condition, a strategy for targeted and evidence-based Nursing action. The central concept that emerged was <Nursing care for children with congenital heart disease=. Furthermore, the following Metaparadigm concepts were identified (N=04): Person, Health, Environment and Nursing; Linked Concepts (N=03): Illness, Family and Caregiver and; Procedural Concepts (N=04): Cardiological Assessment; Preventive Care; Intensive Care; Palliative Care. Seven propositions were determined, namely: person, health, environment, nursing, illness, family and caregiver. And also composed of the concepts of the Metaparadigm, as well as linked concepts. The assumptions of the TMA were totaled in seven, covering nursing care for children with congenital heart disease, nursing and assessment team, care, educational and management technologies, assessment instruments and specialized training. In the concept of cardiological assessment, care focused on nutritional status and weight, oximetry and warning signs of cardiovascular health/disease were identified; in intensive care monitoring of oxygenation and mechanical ventilation, maintenance of body temperature, administration and management of vasoactive drugs, blood components and blood products, perioperative surgery cardiac and hemodynamic stabilization; preventive care with the prevention of anemia, infections and cardiovascular and respiratory complications, growth and development and promotion of breastfeeding, nutrition and vaccination. Finally, palliative care with embracement and a focus on transition, self-care and the culture of the child, family and caregiver. The Theory of Nursing Care for Children with Congenital Heart Disease, the findings that characterize the constructed theory, such as the purpose, propositions, layout and assumptions were listed, as well as the practical application of the theory based on the mapping of nursing care identified in the study and systematized based on theory with nursing interventions from the International Classification for Nursing Practice. After testing the hypothesis, the thesis was proven and the development of a TMA was applied to Nursing Care for Children with Congenital Heart Disease through research induction.